The Role of Urban Cemeteries in Ecosystem Services and Habitat Protection - Ágnes Sallay; Imola Gecséné Tar; Zsuzsanna Mikházi; Katalin Takács; Cecilia Furlan; Ulrike Krippner (Plants, 2023)
Cemeteries, like urban public parks, are an important part of the urban ecosystem, providing semi-natural habitats for many plant and animal species as well as a wide range of ecosystem services: they improve air quality, reduce the urban heat island phenomenon and provide aesthetic and recreational value. This paper explores the role of the cemeteries in the green infrastructure network beyond their sacred and memorial role and their importance as a habitat for urban flora and fauna. In our study, we compared two large public cemeteries of Budapest (Nemzeti Sírkert/National Graveyard and Új Köztemető/New Public Cemetery) with the Zentralfriedhof Wien (Central Cemetery of Vienna), the latter of which has been forward-looking in terms of green infrastructure development and habitat creation in the past years. Our goal was to determine which maintenance technologies and green space development methods are most beneficial in terms of sustainable habitat creation and the use of appropriate plant species in public cemeteries.